How can the connection model for integrating Information and Communication Technology solve four major grade 12 accounting problems? - Sithole, Nosihle Veronica (Universitas Majalengka, 2025)
There are several problems that affects the quality of teaching and learning in accounting in secondary schools. In grade 12 particularly, English language misunderstanding, limited advance teaching skills and abilities, restricted teaching times and lack of parental support have been observed as major problems that hinders quality teaching and causes poor academic performance. Therefore, this study aimed to demonstrate how the connection model for integration of Information and Communication Technology can solve these four major grade 12 accounting problems. Actor Network Theory (ANT) informed this empirical inquiry. In addition, critical paradigm and Participatory Action Research were used to understand the research phenomenon. Six teachers were purposively sampled to participate in the discussion and the data collected was analysed using a content analysis. Results showed that connection model can solve the four major problem in grade 12 by offering opportunities of communicating in one language and using auto-correct to improve vocabulary. Through reinforcing technological knowledge and skills for new pedagogical ideas. Furthermore, by providing an alternative convenient learning method and connecting teachers with parents via WhatsApp. Considering the above results, the study suggested that connection model must be more embraced in accounting. The model must be documented and made available to accounting teachers to also use it for ICT integration in accounting. It is recommended that the connection model should be developed into an app for accounting.